A Text Book Of Biotechnology - R.C. Rubey; R.C. Rubey (New Delhi S. Chand & Company LMT)
This book provides Biotechnology, and scope and its important.
Biotechnology Genitic engineering Gene Concept
Keywords: Biotechnology; Genitic engineering; Gene Concept